Metals in Two Species of Fish in Karasu River - Sonmez, Adem Yavuz; Yağanoğlu, Aycan Mutlu; Hisar, Olcay; Arslan, Gökhan (Springer Science and Business Media LLC, 2012)
In this study, cadmium (Cd), copper (Cu), iron (Fe), nickel (Ni), lead (Pb) and zinc (Zn) levels were determined in the tissues (muscle, liver and gills) of two fish species, Capoeta capoeta umbla and Chalcalburnus mosullensis, collected from three stations of the Karasu River. The lowest metal accumulation was detected in the muscle tissues. Moreover there was some variability in the metal concentrations measured in the same tissues from samples obtained from the three different stations. A positive correlation was observed for the concentration of metal pairs Fe-Cu, Fe-Zn, Ni-Pb, Pb-Zn. These findings were also compared with national and international food standards, and Pb and Cd concentrations were determined to be above the level set by the standards. In conclusion, it was supposed that excessive consumption of these two fish species, which already occurs in this region, might pose a public health risk.
Keywords: Turkey; Cyprinidae; Food Contamination; Risk Assessment; Rivers; Metals; Water Pollution, Chemical; Animals; Water Pollutants, Chemical; Environmental Monitoring; 6. Clean water; 14. Life underwater